2014
DOI: 10.1080/01488376.2014.980963
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Outside the Box: Community-Based Social Service Provider Experiences With Using an Alcohol Screening and Intervention

Abstract: Objective The aim of this study is better understand perceptions of front-line social service workers who are not addiction specialists, but have to address addiction-related issues during their standard services. Method Six social service organizations implemented a validated alcohol assessment and brief education intervention. After a 3-month trial implementation period, a convenience sample of 64 front-line providers participated in six focus groups to examine barriers and facilitators to the implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This finding is supported by extant literature that yields similar results within facilities that treat SUDs 21,41,42 as well as gaps in wider mental health and psychiatric training and education. [7][8][9][10][11] It should be noted that some participants had more prior experience with group CBT manuals than others before leading groups, either at the current or past facilities, which led to a deeper understanding of CBT principles. Nevertheless, the lack of training caused difficulties adapting the needs and requirements of the manual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported by extant literature that yields similar results within facilities that treat SUDs 21,41,42 as well as gaps in wider mental health and psychiatric training and education. [7][8][9][10][11] It should be noted that some participants had more prior experience with group CBT manuals than others before leading groups, either at the current or past facilities, which led to a deeper understanding of CBT principles. Nevertheless, the lack of training caused difficulties adapting the needs and requirements of the manual.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] It is suggested that one of the greatest contributors to this low level of uptake is the lack of proper training and education among healthcare professionals to administer EBP within healthcare facilities. 5,[7][8][9][10][11][12] Therefore, implementation alone is simply not enough to ensure that new practices are being adequately adopted into routine care. 13 Consequently, dynamic, multi-pronged, multi-stakeholder implementation strategies are necessary to enhance adaptation and sustainment of a certain innovation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation